Eksistensi Tradisi Mupunjung Situs Lengkong Ciilat Desa Sukadana Kecamatan Sukadana Kabupaten Ciamis - Ahmad Rizky Fauzi (Jurnal Tamaddun, 2023)
The existence of the Mupunjung tradition which still exists today is an interesting study material for writers. Mupunjung comes from the word munjung or ngunjung. Mupunjung has many meanings such as "full to beyond capacity", coming, asking, and offering prayers. after the entry of the Islamic religion, the Mupunjung tradition became one of the worship activities, namely pilgrimage and Tawasulan. The event is held once a year every Wednesday or Thursday in the month of Ruwah. The research method used is a qualitative method with an ethnographic approach. Data collection techniques through observation, interviews, and document studies. This research uses primary and secondary data sources. Primary data sources were obtained from observations and interviews, while secondary data sources were obtained from supporting documents in the form of photographs and research reports with the same research subject. The results showed that the Mupunjung procession was: (1) preparation, and (2) implementation which consisted of opening, greeting, prayer/tawasul and botram (meal together). The people of Dusun Ciilat always work together and support one another in carrying it out.